Saltbush (Atriplex nummularia L.) reduces efficiency of rumen fermentation in sheep - Mayberry D.E.; Masters D.G.; Vercoe P.E. (Nutritional and foraging ecology of sheep and goats, 2009)
In a preliminary experiment, in vitro methane production in rumen fluid from sheep fed old man saltbush (Atriplex nummularia) was approximately four times higher than methane production in rumen fluid from sheep fed straw or a mixed oaten-hay and lupin ration. To understand this result further we tested the hypotheses that in vivo methane production would be higher in sheep fed saltbush compared to sheep fed a traditional forage, and that the increase in methane production would be due to the high level of salt in saltbush. Forty merino wethers (average weight 43 kg) with no previous experience on salty diets were allocated to one of four treatment diets; control pellet of wheaten chaff, barley, oats and lupins (NS), control pellet + 10% salt (MS), control pellet + 20% salt (HS), or saltbush leaves containing approximately 16% salt (SB). The salt in all diets was approximately 2NaCl:1KCl, and sheep had free access to fresh drinking water at all times. Measurements were taken after sheep had been fed the diets for a minimum of two weeks, and included methane production over a 22-hour period, the number of methane-producing archaea in the rumen, and volatile fatty acid production. Sheep fed saltbush produced more methane (l/22h/kg DOMI), had higher numbers of methane-producing archaea and a higher ratio of acetate to propionate in the rumen. There was no difference in these measurements between the NS, MS and HS treatments. We conclude that the reduction in efficiency of rumen fermentation is not related to the salt content of the forage, but may explain why animal production from saltbush pastures is poor.
12. Seminar on: Nutritional and Foraging Ecology of Sheep and Goats, 2007/10/11-13, Thessaloniki (Greece)